2004
DOI: 10.1007/s00423-003-0449-4
|View full text |Cite
|
Sign up to set email alerts
|

Accessory spleens: preoperative diagnostics limitations and operational strategy in laparoscopic approach to splenectomy in idiopathic thrombocytopenic purpura patients

Abstract: We conclude that the problem of accessory spleens can be managed by careful videoscopic examination of the abdominal cavity during splenectomy, while the use of preoperative imaging techniques in detection of accessory spleens is still limited by the insufficient sensitivity of the examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
0
20
1
5
Order By: Relevance
“…However the value of preoperative imaging to detect AcS remains unclear. Stanek et al (16) found a level of sensitivity of the preoperative CT scan in the 43% of the cases. This lack of sensitivity can be caused by insufficient resolution of the imaging or by the missing of the small accessory organ most frequently located adjacent to the main spleen.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However the value of preoperative imaging to detect AcS remains unclear. Stanek et al (16) found a level of sensitivity of the preoperative CT scan in the 43% of the cases. This lack of sensitivity can be caused by insufficient resolution of the imaging or by the missing of the small accessory organ most frequently located adjacent to the main spleen.…”
Section: Discussionmentioning
confidence: 95%
“…Stanek et al (16) report the recurrence of ITP in 9% of patients; in all cases the presence of splenic tissue was proved by scinthigraphy. Three additional accessory spleens were also identified and excised in three cases in which no preoperative data of their presence were present.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…First, we believe that an appropriate and meticulous surgical technique, including bipolar coagulation, harmonic scalpel, or LigaSure Ò device, seems sufficient to avoid bleeding, even in patients with a very low level of platelets, which has been shown by the experience of many surgical centers, as well as ours [5].…”
mentioning
confidence: 93%
“…[2,4] Following splenectomy, upto 80% of patients will have a response rate characterized by an elevation in platelet count. [5,6] Laparoscopic splenectomy (LS) was first reported in 1992. [7] Now LS is the standard procedure for many hematological diseases including ITP.…”
mentioning
confidence: 99%